(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, we can see that the Jadids tried to find the basis for the social, cultural and educational development of the country in the past of the people, and sought to trace the innovations created by our ancestors in the past, and their own views in a certain way. In addition, the Jadids analyzed that in order to achieve progress, every Muslim should master the secrets of science and life experiences left by their ancestors, and based on these experiences, introduce today’s modern changes to their country.